Diagnostic accuracy of Alvarado scoring system relative to histopathological diagnosis for acute appendicitis: A retrospective cohort study. (September 2022) - Naeem, Muhammad Tayyab; Jamil, Muhammad Amir; Anwar, Muhammad Imran; Raza, Hassan; Asad, Ali; Jamil, Hashaam; Tahir, Muhammad Junaid; Bai, Jharna; Ejaz Chauhan, Tabssum Mohamad; Asghar, Muhammad Sohaib
Abstract: Background: Acute appendicitis (AA) is a surgical emergency that requires prompt diagnosis and suitable management. It may lead to complications resulting in mortality. To evaluate the diagnostic accuracy of the Alvarado scoring system (ASS) for acute appendicitis concerning histopathological data. Methodology: About 120 patients were selected for this study consisting of 96 males and 24 females age between 20 and 60. Alvarado scoring system is calculated for each patient after collecting data about demographics, laboratory findings, and clinical examination. Then, we compared it with histopathological diagnosis taking it as a gold standard. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. SPSS version 20 was used for analyzing the data. Results: About 120 patients were included in our study. The male to female ratio was 3:1. Sensitivity and specificity were 83.3% and 41% respectively. While PPV and NPV were 85% and 41% respectively. The negative appendectomy rate was 21%. The area under the curve for receiving operating characteristics is 0.628. Conclusion: ASS is a useful diagnostic tool regarding sensitivity and positive predictive value, especially in developing countries. It is cheap, reliable, and can be easily applied. Highlights: We evaluated the diagnostic accuracy of the Alvarado scoring system (ASS) for acute appendicitis. Sensitivity and specificity were 83.3% and 41%. While PPV and NPV were 85% and 41% respectively.